From macro to micro: how do Brazilian educational normative documents guide creativity? - Oliveira, Hênio Delfino Ferreira de; Boscarioli, Clodis; Vertuan, Rodolfo Eduardo (Educação Matemática Debate, 2025)
What are the normative guidelines for creativity in Basic Education? Based on an analysis of six Brazilian normative educational documents (LDB, DCN, BNCC, BNCC Computing, BNC-Formação and BNC-Formação Continuada), we sought to understand how creativity is addressed at the macro (institutional) and micro (pedagogical practices) levels. Methodologically, the investigation began by reading the titles of chapters and sections of the documents, followed by searching for keywords, such as create and creativity, and then analyzing the corresponding excerpts. The results show that although creativity is mentioned, its presence in teaching practice is limited. It is concluded that a continuous and strategic effort is needed to expand and make its inclusion more effective through both public policies and pedagogical practices.